From the Pedagogy Course to the School of Education/PUCRS: (Porto Alegre/RS - 1942-2015) - Maria Helena Camara Bastos (Universidade Federal do Rio Grande do Sul, 2016)
The article analyzes the history of the Pedagogy Course and of the School of Education of the Pontifical Catholic University of Rio Grande do Sul since 1942, when it was founded. In order to analyze the 73-year trajectory of the Pedagogy Course and the 47 years of the School of Education, we must always remember the articulation with the national and local context, the legislation and reformulations of higher and university education during this period. This study makes use of several perspectives: the provided Pedagogy course and training, the School and the undergraduate and post-graduate courses, the Educação and Educação por Escrito journals. It is concluded by analyzing the challenges of the Pedagogy course as a part of the School of Humanities, from 2016 onwards.